Investigating the performance and emission characteristics of sunflower biodiesel blends with n-butyl and isopropyl alcohol additives - Shunmugesh K.; Anaz Khan Muhammed; Joby Joseph; Balram Yelamasetti; Harinadh Vemanaboina; Prabhu Paramasivam (AIP Advances)
This study investigates the potential of sunflower seed oil biodiesel as a renewable fuel source. The study focuses on the development of BD25 sunflower biodiesel blends and their impact on emissions and performance characteristics compared to diesel fuel. Sunflower seed oil undergoes transesterification with methanol and KOH, yielding biodiesel and glycerol. Due to its high oil content, sunflower oil is a promising feedstock for biodiesel production. The BD25 blend is prepared by mixing 250 ml of sunflower biodiesel with 750 ml of diesel. Furthermore, seven additional blends are formulated by incorporating n-butyl alcohol and isopropyl alcohol additives in varying proportions (5, 10, and 15 ml) within the BD25 base. These blends are then evaluated in a single-cylinder DI diesel engine at a constant speed of 2500 rpm. The study comprehensively analyzes various engine parameters, including initial and final weight, air–fuel ratio, exhaust gas temperature, and regulated emissions (CO, HC, CO2, and NOx). The addition of alcohol additives demonstrates the potential to reduce smoke opacity and hydrocarbon emissions, particularly at low engine speeds. By comparing the emission and performance characteristics of the biodiesel blends with diesel fuel, the study aims to assess the feasibility of large-scale sunflower oil biodiesel production as a viable alternative fuel source.